2018
DOI: 10.2147/ijn.s170819
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the surface of titanium with multifunctional chimeric peptides to prevent biofilm formation via inhibition of initial colonizers

Abstract: BackgroundPrevention of bacterial colonization remains a major challenge in the field of oral implant devices. Chimeric peptides with binding, antimicrobial, and osteogenesis motifs may provide a promising alternative for the inhibition of biofilm formation on titanium (Ti) surfaces.MethodsIn this study, chimeric peptides were designed by connecting an antimicrobial sequence from human β-defensin-3 with a Ti-binding sequence and arginine-glycine-aspartic acid using a glycine-glycine-glycine linker. Binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
(38 reference statements)
0
31
0
Order By: Relevance
“…In our previous study, we used Ti-binding peptide (RKLPDAPGMHTW) as a means to introduce antimicrobial (GKCSTRGRKCCRRKK) and osteogenesis-promoting groups (RGDS) on Ti surface. 29,30 It was proved to be a simple and feasible modication strategy. Proteins perform their functions mainly through the structural stabilization of functional domains in secondary protein structures.…”
Section: Design Of Chimeric Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we used Ti-binding peptide (RKLPDAPGMHTW) as a means to introduce antimicrobial (GKCSTRGRKCCRRKK) and osteogenesis-promoting groups (RGDS) on Ti surface. 29,30 It was proved to be a simple and feasible modication strategy. Proteins perform their functions mainly through the structural stabilization of functional domains in secondary protein structures.…”
Section: Design Of Chimeric Peptidesmentioning
confidence: 99%
“…Although these antimicrobial peptides caused leakage of intracellular content, the results of cytotoxicity experiments showed that the three chimeric peptides exhibited no signicant cytotoxicity toward MC3T3-E1 cells. 29,30 Our previous studies have shown that chimeric peptides can inhibit the formation of biolm by inhibiting gene expression. 29,30 However, more extensive studies have not yet been undertaken to clarify the same.…”
Section: Comparison Of the Structure And Function Of Chimeric Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Titanium (Ti) is one the most frequently applied materials for dental implants due to their excellent osteocompatibility, mechanical property and corrosion resistance (1)(2)(3). The oral cavity is a humid environment that provides a habitat for acid-producing bacteria, which causes low pH around the implants (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%